History teachers' experiences on peace education - Akif Pamuk; Cahide Kayış (Turkish History Education Journal, 2022)
The aim of this research is to find out the views of history teachers on peace education. The research consists of four sub-problem sentences. For this purpose, teachers' opinions were sought on the contribution of history teaching/history textbooks/values and historical thinking skills to peace education. At the same time, teachers' experiences in history lessons are also included in the context of peace education. The study group of the research consists of 19 history teachers working in public and private schools affiliated to the Ministry of National Education in various districts of Istanbul. In this study, the qualitative research method was preferred, and Phenomenology (phenomenology) was chosen from qualitative research designs in order to reveal the experiences of the teachers who may be a party to the problem of the research. The data of the research consists of teacher opinions obtained through interviews and focus group interviews. The data were recorded with a voice recorder and transcribed. Content analysis and descriptive analysis methods were used in the analysis of the data obtained. Findings reveal that teachers generally think that history teaching can contribute positively to peace education. In the context of the contribution of history textbooks to peace education, teachers have expressed that they can contribute both positively and negatively. When the experiences of history teachers in history lessons are examined, the categories of student prejudices, students' belonging to their identity, students' collective memory, and choosing sides have emerged. Among these categories, student prejudices and belonging to student identities have a high frequency. Considering the historical thinking skills, it comes to the fore that peace education will contribute positively to the research skills based on historical empathy and inquiry, and to the value of respect within the scope of values.